ANALISIS NILAI TAMBAH PENGOLAHAN GULA KELAPA DI KABUPATEN OKU TIMUR - Ary Eko Prastya Putra (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2017)
The purposes of this research were to : (1) To calculate the amount of production cost that is expended and income earned in coconut sugar processing business in East OKU Regency, (2) To know the value of coconut sugar processing in East OKU Regency, (3) To know the level of coconut sugar business feasibility in East OKU Regency. This research was conducted in OKU Timur Regency, but there were only two sub-districts from 20 sub-districts doing coconut sugar processing business. Namely Belitang District III and Belitang Mulya District. For Belitang III District, there is one village that conducts coconut sugar processing business, that is Desa Switchwarno, and for Belitang Mulya Sub-district there are 5 villages doing coconut sugar processing business, namely Sugih Waras Village, Petanggan Village, Rejosari Village, and Srimulyo Village. Determining the location is done purposively (purposive sampling) with the consideration that in 5 villages are doing palm sugar processing business. While field research will be conducted in April 2013 until the completion. This research found that the production cost of coconut sugar processing business in East OKU Regency in one month of production is Rp 2,707,071.43 or Rp 32,484,857.16 / year, and the income earned in one business year is Rp 20,015,142,84 / year. The added value of coconut sugar processing business in OKU Timur Regency in one month of business is Rp 3,325,428.57 and Coconut sugar processing business in East OKU district is feasible to be developed with NPV value for 4 years ahead Rp 27,823,216.06, IRR 22.04% and Net B / C 1.61.